Sodium-rich positive electrode material, preparation method, battery and application of sodium-rich positive electrode material

When preparing the sodium-rich positive electrode material Na1+xCr1-xO2, sodium acetate is excessively relative to chromium acetate and adopts specific preparation steps, the structural instability problem caused by irreversible migration of chromium ions is solved, high specific capacity and stability are achieved, and the The production cost is suitable for sodium ion batteries.

CN119191351APending Publication Date: 2024-12-27GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411279735.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing positive electrode materials have structural instability due to the irreversible migration of chromium ions under high charging cutoff voltage, which limits the development of sodium ion batteries, and doping technology increases production costs and process difficulty.

Method used

When preparing the sodium-rich cathode material Na1+xCr1-xO2, sodium acetate is appropriately excessive compared with chromium acetate, forming a wide electrochemical window, and using steps such as liquid nitrogen frozen and muffle furnace heat treatment to ensure the multi-electron redox reaction of chromium ions. and reversible migration reduce structural instability.

Benefits of technology

High specific capacity and good crystal structure stability under a wider electrochemical window are achieved, reducing production costs and avoiding the problems of difficult and high cost of processing of doping technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191351A_ABST
    Figure CN119191351A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-rich positive electrode material, a preparation method, a battery and application thereof. The preparation method comprises the following steps: dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a mixed solution, placing the mixed solution in a water bath kettle, and heating the mixed solution to a gel state to obtain wet gel; the molar mixing ratio of the sodium acetate to the chromium acetate is (1 + x): (1-x) (x is more than or equal to 0.1 and less than or equal to 0.3); quickly freezing the obtained wet gel with liquid nitrogen, and performing freeze drying treatment in a freeze dryer to obtain dry gel; grinding and refining the dry gel; placing the dry gel in a muffle furnace, and performing low-temperature heat treatment to obtain sodium chromate powder; and calcining the sodium chromate powder in a reducing atmosphere at the temperature of 800-1000 DEG C to obtain the sodium-rich positive electrode material Na < 1 + x > Cr < 1-x > O < 2 >. The sodium-rich positive electrode material in the scheme can realize stable electrochemical reversibility in a wide electrochemical window, shows excellent electrochemical performance, and solves the problems of high processing difficulty and high cost in the existing doping technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of positive electrode materials, and in particular to a sodium-rich positive electrode material, a preparation method, a battery and uses thereof. Background Art

[0002] Lithium-ion batteries are considered the most promising battery technology for portable electronic devices and electric vehicles due to their high energy density, high energy conversion efficiency and simple maintenance. However, the emerging lithium-ion battery market is inevitably constrained by limited lithium resources and unpredictable price fluctuations. Therefore, it is particularly important to find an alternative to lithium-ion batteries to adapt to the large-scale new energy device market. As a new generation of large-scale energy storage devices, sodium-ion batteries are abundant in resources, cheap, and have a similar working principle to sodium-ion batteries. They are expected to replace lithium-ion batteries and become the mainstream of the next generation of new energy storage batteries.

[0003] The selection of cathode materials is the main reason restricting the development of sodium-ion batteries. Among the many cathode materials, layered oxide NaCrO2 has a high theoretical specific capacity (250 mAh g -1 ), good electrochemical reversibility and fast sodium ion diffusion kinetics. However, high charging cut-off voltage will cause irreversible migration of chromium in the transition metal layer, causing structural instability. To avoid this, the current charging cut-off voltage of NaCrO2 is generally less than 3.6V. At this time, about 0.5 mol Na + Ions can be reversibly deintercalated and deintercalated, corresponding to a specific capacity of about 120 mAh g -1 , only half of the theoretical specific capacity. Based on this, many scholars have expanded its operating voltage window and inhibited the irreversible migration of chromium metal ions by doping elements at Na, Cr and O sites. Although element doping can broaden the electrochemical window and improve the specific capacity to a certain extent, element doping will increase production costs, increase process difficulty, and limit its practical application. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a sodium-rich positive electrode material, wherein the sodium acetate is appropriately excessive relative to the chromium acetate in the raw material ratio. 1+x Cr 1-x O2 cathode materials exhibit excellent electrochemical properties such as high specific capacity within a wide electrochemical window.

[0005] The present invention also provides a sodium-rich positive electrode material, which uses the above-mentioned preparation method.

[0006] The invention also proposes a use of a sodium-rich positive electrode material in preparing a battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A method for preparing a sodium-rich positive electrode material comprises the following steps:

[0009] (1) dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a mixed solution, which is then placed in a water bath and heated until it becomes a gel state to obtain a wet gel;

[0010] The molar mixing ratio of sodium acetate to chromium acetate is (1+x):(1-x)(0.1≤x≤0.3);

[0011] (2) freezing the obtained wet gel with liquid nitrogen, and then placing it in a freeze dryer for freeze drying to obtain a dry gel;

[0012] (3) grinding and refining the xerogel;

[0013] (4) placing the dry gel in a muffle furnace and subjecting it to heat treatment to generate sodium chromate powder; the heat treatment temperature of the muffle furnace is 300 to 500° C., the temperature is maintained for 1 to 3 hours, the heating rate is 1 to 5° C. / min, and then the dry gel is cooled with the furnace;

[0014] (5) In a tube furnace, sodium chromate powder is calcined in a reducing atmosphere at a temperature of 800 to 1000°C to obtain a sodium-rich positive electrode material Na 1+x Cr 1-x O2.

[0015] Optimally, in step (1), the concentration of the mixed solution is 10 to 40 g / L; in step (2), the freeze-drying treatment time is 12 to 16 hours.

[0016] Preferably, in step (5), the reducing atmosphere is a mixed gas of an inert gas and hydrogen, and the hydrogen content in the reducing gas is 5-10 Vol%.

[0017] Preferably, in step (5), when the calcination temperature is increased from room temperature to the highest temperature, the heating rate is 1 to 5°C / min, the highest temperature is kept for 8 to 12 hours, and the calcination temperature is then decreased from the highest temperature to room temperature at a cooling rate of 1 to 5°C / min.

[0018] A sodium-rich positive electrode material is prepared by the above-mentioned method for preparing a sodium-rich positive electrode material.

[0019] A use of a sodium-rich positive electrode material in preparing a battery, wherein the sodium-rich positive electrode material is prepared by the above-mentioned method for preparing a sodium-rich positive electrode material.

[0020] A battery uses the above-mentioned sodium-rich positive electrode material.

[0021] Compared with the prior art, one of the above technical solutions has the following beneficial effects:

[0022] The present invention provides a method for preparing a sodium-rich positive electrode material. The sodium acetate, chromium acetate and citric acid are initially prepared so that the sodium acetate is in excess relative to the chromium acetate. 1+x Cr 1-x O2 can achieve stable electrochemical reversibility within a wide electrochemical window, exhibiting excellent electrochemical performance, and solving the problems of high processing difficulty and high cost of existing doping technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The sodium-rich cathode material Na prepared in Example 1 1.1 Cr 0.9 Scanning electron microscope (SEM) image of O2.

[0024] Figure 2 The sodium-rich cathode material Na prepared in Example 2 1.3 Cr 0.7 X-ray diffraction (XRD) pattern of O2

[0025] Figure 3 The sodium-rich cathode material Na prepared in Example 3 1.2 Cr 0.8 The first charge and discharge curve test diagram of O2 assembled into a sodium ion battery;

[0026] Figure 4 The sodium-rich cathode material Na prepared in Example 3 1.2 Cr 0.8 O2 assembled into a sodium ion battery cycle performance test diagram;

[0027] Figure 5 The sodium-rich cathode material Na prepared in Example 3 1.2 Cr 0.8 Rate performance test diagram of O2 assembled into sodium-ion battery. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0029] For ease of understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the documents in this area or the product instructions are carried out. The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be obtained by commercial purchase.

[0030] A method for preparing a sodium-rich positive electrode material comprises the following steps:

[0031] (1) dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a mixed solution, which is then placed in a water bath and heated until it becomes a gel state to obtain a wet gel;

[0032] The molar mixing ratio of sodium acetate to chromium acetate is (1+x):(1-x)(0.1≤x≤0.3);

[0033] After the solution of step (1) is prepared, it is placed in a water bath, citric acid is used as a complexing agent to react with metal ions to form a complex, and the water in the solution is slowly evaporated to form a wet gel;

[0034] (2) freezing the obtained wet gel with liquid nitrogen, and then placing it in a freeze dryer for freeze drying to obtain a dry gel;

[0035] (3) grinding and refining the xerogel;

[0036] (4) placing the dry gel in a muffle furnace and subjecting it to heat treatment to obtain sodium chromate powder; the heat treatment temperature of the muffle furnace is 300 to 500° C., the heat treatment is maintained for 1 to 3 hours, and the heating rate is 1 to 5° C. / min;

[0037] (5) calcining sodium chromate powder in a reducing atmosphere at a temperature of 800 to 1000° C. to obtain a sodium-rich positive electrode material Na 1+x Cr 1-x O2.

[0038] The present invention provides a method for preparing a sodium-rich positive electrode material, wherein sodium acetate, chromium acetate and citric acid are initially prepared so that sodium acetate is in excess relative to chromium acetate to form a sodium-rich Na 1+x Cr 1-x O2 positive electrode material can achieve stable electrochemical reversibility within a wide electrochemical window, exhibiting excellent electrochemical performance, and solving the problems of high processing difficulty and high cost of existing doping technology.

[0039] The sodium-rich cathode prepared according to the above steps in this scheme can realize the multi-electron redox reaction of chromium ions and the reversible migration between octahedral and tetrahedral positions during the charge and discharge process. Therefore, the sodium-rich cathode oxide has a higher specific capacity and better crystal structure stability. Based on this, the sodium-rich cathode material obtained by the present invention can work in a wider electrochemical window and show excellent electrochemical performance.

[0040] Optimally, in step (1), the concentration of the mixed solution is 10 to 40 g / L; in step (2), the freeze-drying treatment time is 12 to 16 hours.

[0041] Preferably, in step (5), the reducing atmosphere is a mixed gas of an inert gas and hydrogen, and the hydrogen content in the reducing gas is 5-10 Vol%.

[0042] The reducing atmosphere used in this solution is a mixture of inert gas and hydrogen, such as argon-hydrogen mixed gas, nitrogen-hydrogen mixed gas or helium-hydrogen mixed gas. The volume ratio of hydrogen in the mixed gas is 5-10 Vol%.

[0043] Preferably, in step (5), when the calcination temperature is increased from room temperature to the highest temperature, the heating rate is 1 to 5°C / min, the highest temperature is maintained for 8 to 12 hours, and the calcination temperature is then decreased from the highest temperature to room temperature at a cooling rate of 1 to 5°C / min.

[0044] When calcining sodium chromate powder in this scheme, the optimal heating rate is 1-5°C / min and the cooling rate is 1-5°C / min. The heating and cooling rates are stable, which can ensure that the particles are relatively uniform, with a diameter of approximately 0.2-1 μm, and the particles are free of impurities, high purity and good crystallinity.

[0045] A sodium-rich positive electrode material is prepared by the above-mentioned method for preparing a sodium-rich positive electrode material.

[0046] A use of a sodium-rich positive electrode material in preparing a battery, wherein the sodium-rich positive electrode material is prepared by the above-mentioned method for preparing a sodium-rich positive electrode material.

[0047] A battery using a sodium-rich positive electrode material according to any of the above embodiments.

[0048] Embodiment 1:

[0049] A method for preparing a sodium-rich positive electrode material, comprising:

[0050] (1) dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a 20 g / L mixed solution; heating the mixed solution in a water bath and evaporating it to a gel state; the molar mixing ratio of sodium acetate, chromium acetate and citric acid is 1.1:0.9:1;

[0051] (2) The obtained wet gel was frozen with liquid nitrogen and then placed in a freeze dryer for 12 h to obtain a dry gel;

[0052] (3) grinding and refining the xerogel;

[0053] (4) The dry gel was placed in a muffle furnace and heat treated at 450°C for 2 h at a heating rate of 5°C / min, and then cooled in the furnace;

[0054] (5) In a tubular furnace, a mixed gas of argon and hydrogen was introduced for 30 minutes, with a hydrogen content of 5 Vol%. Then, the temperature was raised from room temperature to 800°C at a heating rate of 5°C / min, and kept at this temperature for 10 hours. Then, the temperature was lowered from 800°C to room temperature at a cooling rate of 1°C / min to obtain a sodium-rich positive electrode material Na 1.1 Cr 0.9 O2.

[0055] The sodium-rich positive electrode material obtained in Example 1 was observed under a scanning electron microscope. Figure 1 As shown, the particles are irregular polygonal in shape, and the particle size is relatively uniform, with the particle size being approximately between 0.2 and 1 μm;

[0056] Embodiment 2:

[0057] A method for preparing a sodium-rich positive electrode material, comprising:

[0058] (1) dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a 30 g / L mixed solution; heating the mixed solution in a water bath and evaporating it to a gel state; the molar mixing ratio of sodium acetate, chromium acetate and citric acid is 1.3:0.7:1;

[0059] (2) The obtained wet gel was quickly frozen with liquid nitrogen and then placed in a freeze dryer for freeze drying for 14 h to obtain a dry gel;

[0060] (3) grinding and refining the xerogel;

[0061] (4) placing the dry gel in a muffle furnace at 500°C for heat treatment, keeping the temperature for 1 h, with a heating rate of 3°C / min, and then cooling in the furnace;

[0062] (5) In a tubular furnace, a nitrogen and hydrogen mixed gas was introduced for 30 minutes, with a hydrogen content of 10 Vol%. Then, the temperature was raised from room temperature to 900°C at a heating rate of 3°C / min, and kept at this temperature for 8 hours. Then, the temperature was lowered from 900°C to room temperature at a cooling rate of 2°C / min. The sodium-rich positive electrode material Na 1.3 Cr 0.7 O2.

[0063] XRD analysis was performed on the sodium-rich cathode material prepared in Example 2. The results are as follows: Figure 2 As shown, it is shown that the sodium-rich material prepared in Example 2 has no impurity phase, high purity and good crystallinity.

[0064] Embodiment 3:

[0065] A method for preparing a sodium-rich positive electrode material, comprising:

[0066] (1) dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a 40 g / L mixed solution; heating the mixed solution in a water bath and evaporating it to a gel state; the molar mixing ratio of sodium acetate, chromium acetate and citric acid is 1.2:0.8:1;

[0067] (2) The obtained wet gel was quickly frozen with liquid nitrogen and then placed in a freeze dryer for freeze drying for 16 h to obtain a dry gel;

[0068] (3) grinding and refining the xerogel;

[0069] (4) placing the dry gel in a muffle furnace at 300°C for 3 h at a heating rate of 4°C / min, and then cooling in the furnace;

[0070] (5) In a tubular furnace, a mixed gas of helium and hydrogen was introduced for 30 minutes, with a hydrogen content of 8 Vol%. Then, the temperature was raised from room temperature to 1000°C at a heating rate of 1°C / min, and kept at this temperature for 12 hours. Then, the temperature was lowered from 1000°C to room temperature at a cooling rate of 4°C / min to obtain a sodium-rich positive electrode material Na 1.2 Cr 0.8 O2.

[0071] The electrochemical performance of the sodium-ion battery composed of the sodium-rich positive electrode material prepared in Example 3 was tested as follows: the electrochemical test was performed using a CR2032 button half-cell. The electrode was composed of the sodium-rich positive electrode material prepared in Example 3, ethylene black and polyvinylidene fluoride, with a weight ratio of 8:1:1. Metallic sodium was used as the counter electrode, and the test was performed on a LAND CT2001A battery test system with a voltage window of 1.5 to 3.8 V (vs Na / Na + , the theoretical specific capacity is 175 mAh g -1 ).

[0072] The first charge-discharge curve of the sodium-ion battery 2C prepared by the sodium-rich cathode material of Example 3 is as follows: Figure 3 As shown, the first cycle charge capacity at 2C is 140.1mAh g -1 The first cycle discharge capacity is 132.7 mAh g -1 The cycle performance of the sodium ion battery prepared by the sodium-rich cathode material of Example 3 at 2C is as follows: Figure 4 As shown in Figure 2, after 500 cycles at a 2C rate, there is still a capacity retention rate of 50.2%, indicating that the material has good cycle performance. The rate performance results of the sodium ion battery prepared by the sodium-rich positive electrode material of Example 3 are shown in Figure 2. Figure 5As shown, it shows that its rate performance is excellent. This shows that the present invention can replace the element doping modification in the prior art by simply regulating the components of sodium acetate and chromium acetate, and the preparation raw materials are abundant and low in price, which can reduce the preparation cost of the positive electrode material; and the prepared positive electrode material has the advantages of high specific capacity and good crystal structure reversibility, and can be widely used in sodium ion batteries.

[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a sodium-rich positive electrode material, characterized in that: The following steps are involved: (1) dissolving sodium acetate, chromium acetate and citric acid in deionized water to prepare a mixed solution, which is then placed in a water bath and heated until it becomes a gel state to obtain a wet gel; The molar mixing ratio of sodium acetate to chromium acetate is (1+x):(1-x)(0.1≤x≤0.3); (2) freezing the obtained wet gel with liquid nitrogen, and then placing it in a freeze dryer for freeze drying to obtain a dry gel; (3) grinding and refining the xerogel; (4) placing the dry gel in a muffle furnace and subjecting it to heat treatment to obtain sodium chromate powder; the heat treatment temperature of the muffle furnace is 300 to 500° C., the heat treatment is maintained for 1 to 3 hours, and the heating rate is 1 to 5° C. / min; (5) calcining sodium chromate powder in a reducing atmosphere at a temperature of 800 to 1000° C. to obtain a sodium-rich positive electrode material Na 1+x Cr 1-x O2.

2. The method for preparing a sodium-rich positive electrode material according to claim 1, characterized in that: In the step (1), the concentration of the mixed solution is 10 to 40 g / L; in the step (2), the freeze-drying treatment time is 12 to 16 hours.

3. The method for preparing a sodium-rich positive electrode material according to claim 1, characterized in that: In the step (5), the reducing atmosphere is a mixed gas of an inert gas and hydrogen, and the hydrogen content in the reducing gas is 5 to 10 Vol%.

4. The method for preparing a sodium-rich positive electrode material according to claim 1, characterized in that: In the step (5), the calcination temperature is increased from room temperature to the highest temperature at a heating rate of 1 to 5°C / min, maintained at the highest temperature for 8 to 12 hours, and then decreased from the highest temperature to room temperature at a cooling rate of 1 to 5°C / min.

5. A sodium-rich positive electrode material, characterized in that The sodium-rich positive electrode material is prepared by the preparation method of any one of claims 1 to 4.

6. Use of a sodium-rich cathode material in preparing a battery, characterized in that: The sodium-rich positive electrode material is prepared by the method for preparing a sodium-rich positive electrode material according to any one of claims 1 to 4.

7. A battery, characterized in that: Use the sodium-rich positive electrode material described in claim 5.

Citation Information

Patent Citations

  • Flexible self-supporting positive electrode for sodium ion battery as well as preparation method and application of flexible self-supporting positive electrode

    CN114530573A